Polyoxazoline associated with cardanol for bio‐based linear alkyl benzene surfactants. Issue 4 (4th February 2019) - Delage, Benoit; Briou, Benoit; Brossier, Thomas; Catrouillet, Sylvain; Robin, Jean‐Jacques; Lapinte, Vincent
Abstract: Well‐defined linear alkyl benzene surfactants (COx n ) were successfully synthesized using cardanol as a green phenolic alternative and initiator for polyoxazoline (POx), the hydrophilic block of nonionic surfactants. Various hydrophilic lipophilic balance values were investigated by varying the POx length according to the [monomer]/[initiator] ratio. The chemical structure of the surfactants, in particular the terminal groups, was well identified by matrix assisted laser desorption ionization time of flight mass spectrometry demonstrating the good progress of the cationic ring‐opening polymerization. The COx n surfactants spontaneously self‐assembled in water at a critical aggregation concentration of 1–2 µmol L −1 into nano‐objects characterized by a hydrodynamic diameter of 11–24 nm and a number of aggregations ranging from 30 to 60 according to the worm‐like micelle model. © 2019 Society of Chemical Industry Abstract : An alternative to nonyl phenol ethoxylate surfactants is described using cardanol as a bio‐based phenolic building block and polyoxazoline as a polyethylene oxide alternative.